2006
DOI: 10.1111/j.1600-6143.2006.01452.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved Human Islet Isolation Using Nicotinamide

Abstract: We investigated the effects of nicotinamide (NA) supplementation of the processing medium during islet isolation. One hundred and two human pancreata were processed for clinical transplantation after preservation either in the University of Wisconsin (UW) or using the two-layer method (TLM). Pancreata were then divided into four groups and retrospectively analyzed. Group I: UW preservation followed by processing without NA, Group II: UW preservation and processing with NA, Group III: TLM preservation without N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 47 publications
1
59
0
Order By: Relevance
“…with nicotinamide once a day for a 60 days after transplantation, finally, hyperglycemia can be ameliorated with an insufficient under of islet. Furthermore, isolated human or pig islet cells are also cultured in media with 10 mM nicotinamide before transplantation to diabetic recipients (Korsgren et al, 1993;Beattie et al, 2002;Ichii et al, 2006). These findings suggest that nicotinamide may be used to increase the efficiency and effectiveness of pancreatic islet transplantation.…”
Section: Introductionmentioning
confidence: 96%
“…with nicotinamide once a day for a 60 days after transplantation, finally, hyperglycemia can be ameliorated with an insufficient under of islet. Furthermore, isolated human or pig islet cells are also cultured in media with 10 mM nicotinamide before transplantation to diabetic recipients (Korsgren et al, 1993;Beattie et al, 2002;Ichii et al, 2006). These findings suggest that nicotinamide may be used to increase the efficiency and effectiveness of pancreatic islet transplantation.…”
Section: Introductionmentioning
confidence: 96%
“…147 Second, the supplementation of islet isolation solutions with nicotinamide improves the production of high-quality islets for clinical use. 148 Third, our experience using human and rat islet cultures showed that low concentrations of NO protect islets from apoptosis induced by serum withdrawal. 17 Additionally, we have shown that both IGF-1 and insulin promote survival signals that are mediated by NO.…”
Section: Discussionmentioning
confidence: 99%
“…17 Additionally, we have shown that both IGF-1 and insulin promote survival signals that are mediated by NO. 17,104,127 The method of maintenance of the islets 147,148 significantly improves the quality of the islets. However, the use of islet-maintaining agents in islet isolation protocols creates two problems.…”
Section: Discussionmentioning
confidence: 99%
“…1 Despite recent progress, current islet isolation techniques usually require transplantation of islets from two or more donors to establish euglycemia, 2,3 and a transplantable yield of islets is obtained from <50% of all isolations even in advanced islet isolation centers. [4][5][6][7] Successful islet isolation depends on a mechanically enhanced enzymatic digestion to dissociate the extracellular matrix of the islet-exocrine interface to release intact islets. 8 Therefore, it is important to deliver the collagenase to the islet-exocrine interface area properly.…”
Section: Introductionmentioning
confidence: 99%